(untitled) (Práxis Educativa, 2013)
This article discusses the importance of evaluating public policies for education, once it is a recent subject in our country. The first records of this kind of investigation date back the 1980s, originated in stricto sensu post-graduation programs. The epistemological basis focuses on the contributions of the policy cycle theoretical-analytical approach of Stephen Ball and his co-workers, according to whom there are contexts which are conditioned by and also influence the public policies from the opening of their agenda to their implementation. Thus, it is necessary to have an assessment tool which can reveal whether the objective of such policies is achieved or not, considering the contexts under analysis. Regarding the educational field, although Ball’s policy cycle analysis framework is consistent and coherent in terms of validity, radicalism and rigor when applied to the study of policy evaluation, it also constitutes an object of study. Keywords: Policy cycle approach. Educational research. Educational policies.